ENCHANCING DESCRIPTIVE MATERIAL LEARNING AT PUBLIC JUNIOR HIGH SCHOOL THROUGH DIFFEREFTIATED LEARNING AND WIZER.ME E-WORKSHEET - Sari, Dian Eka; Purnomo, Mulyadi Eko; Indrawati, Sri (English Review: Journal of English Education, 2023)
: The aim of this research was to address the challenges posed by changes in regulations for admitting new learners at Public JHS 54 Palembang, where test scores or reports were no longer the primary criteria for enrollment. This research employed a modified model based on the work of Gall, Gall & Borg, and Tessmer. The initial phase involved analyzing the diverse needs of seventh-grade students, encompassing their intentions, profiles, and readiness for learning. The curriculum changes had led to an increased reliance on textbooks, resulting in a need for supplementary worksheets. The researcher used the Canva application to design content within the Wizer.me platform. The validation process included expert validation of the prototype, focusing on material substance. Validation results indicated a high level of approval, with a percentage of 97.3% and a mean score of 4.86. The language aspect received an 86% approval rate, equivalent to an average score of 4.3. Material presentation in the learning materials received a 90% approval rate, with an average score of 4.5, affirming the validity of the developed worksheet.Following expert validation, a small group evaluation was conducted to assess the practicality and reliability of the developed worksheet for descriptive text materials employing differentiated learning. The expert validation results demonstrated that the developed worksheet, created using the Wizer.me application, was highly valid. Additionally, the small group evaluation confirmed that the worksheet was practical and reliable for use in an educational setting. In conclusion, this research successfully addressed the challenges posed by changes in admission regulations at Public JHS 54 Palembang by introducing differentiated learning materials. The use of electronic worksheets, implemented through the Wizer.me platform, proved to be an effective solution for catering to the diverse student profiles. The expert validation and small group evaluation affirmed the validity, practicality, and reliability of the developed worksheet, making it a valuable addition to the educational resources available for seventh-grade students.